2019
DOI: 10.24059/olj.v23i3.2068
|View full text |Cite
|
Sign up to set email alerts
|

From Proprietary Textbook to Custom OER Solution: Using Learner Feedback to Guide Design and Development

Abstract: This study presents the initial needs analysis and formative evaluation of the beta version of an open educational resource (OER) textbook solution. The OER textbook, created by the authors, replaces a proprietary, paper-based textbook and is delivered to students digitally, within a learning management system. Needs analysis findings show that students are concerned about cost and convenience, and are likely to seek course content online before reading material in a traditional course textbook. Many do not pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Among the prominent activities provided by learning management systems are e-teaching materials, which can be presented in different formats. Eteaching materials in the form of open educational resource (OER) textbooks are discussed by Dennen and Bagdy (2019). Their study indicated that students have given positive feedback on OER textbooks and that this type of material contributed to helping them meet course learning objectives.…”
Section: Research On Online Learningmentioning
confidence: 99%
“…Among the prominent activities provided by learning management systems are e-teaching materials, which can be presented in different formats. Eteaching materials in the form of open educational resource (OER) textbooks are discussed by Dennen and Bagdy (2019). Their study indicated that students have given positive feedback on OER textbooks and that this type of material contributed to helping them meet course learning objectives.…”
Section: Research On Online Learningmentioning
confidence: 99%
“…When multiple resources were utilized, there was a related increase in the amount of time it took to prepare the materials for the course. Similar to the experiences at other universities (Dennen & Bagdy, 2019;Dudek et al, 2019;McGreal, 2019), faculty spent time authoring transitional content, developing practice problem sets and case studies, and writing quiz or exam questions and answer keys, as these are typically included in the instructor resources from many commercial textbook publishers. They also spent time preparing tutorial videos that would demonstrate problem or case study solutions.…”
Section: Analysis Of Research Faculty Experiencementioning
confidence: 97%